COVID-19 Burden on HIV Patients Attending Antiretroviral Therapy in Addis Ababa, Ethiopia: A Multicenter Cross-Sectional Study - Chilot, Dagmawi; Woldeamanuel, Yimtubezinash; Manyazewal, Tsegahun (Frontiers in Medicine, 2022)
Background There has been promising progress toward screening, testing, and retaining patients with HIV in care in Ethiopia. Concern exists that possible disruptions in HIV programs due to coronavirus disease 2019 (COVID-19) could result in a more HIV-related mortality and new HIV infections. This study aimed to investigate the real-time burden of COVID-19 on patients with HIV attending antiretroviral therapy. Methods We conducted a facility-based, multicenter, and cross-sectional study among patients with HIV attending antiretroviral therapy in 10 healthcare facilities in Addis Ababa, Ethiopia, in the COVID-19 pandemic period. Data were collected using adapted, interviewer-based questionnaires, and entered into EpiInfo version 7 and exported to SPSS version 26 for analysis. Result A total of 212 patients with HIV were included. The participants who missed visits for refill were 58 (27.4%). When the effects of other independent variables on appointments/visits for refill were controlled, the following characteristics were found to be the most important predictors of missed appointments (p< 0.05): age ≥ 55 [adjusted odds ratio (AOR) = 6.73, 95% CI (1.495–30.310)], fear of COVID-19 [AOR = 24.93, 95% CI (2.798–222.279)], transport disruption [AOR = 4.90, 95% CI (1.031–23.174)], reduced income for traveling to a health facility [AOR = 5.64, 95% CI (1.234-25.812)], limited access to masks [AOR = 7.67, 95% CI (1.303–45.174)], sanitizer [AOR = 0.07, 95% CI (0.007–0.729)], and non-medical support [AOR = 2.32, 95% CI (1.547–12.596)]. The participants were well aware of the COVID-19 preventive measures. The most costly COVID-19 preventive measures that cause financial burden to the patients were the costs for buying face masks (63.7%), disinfectants (55.2%), and soap for handwashing (22.2%). The participants who missed follow-up diagnostic tests were 56 (26.4%). Variables, which were found to be statistically significant, include the following: age ≥ 55 [AOR = 0.22, 95% CI (0.076–0.621)], partial lockdown [AOR = 0.10, 95% CI (0.011–0.833)], limited access to health services [AOR = 0.15, 95% CI (0.045–0.475)], reduced income for traveling to health facility [AOR = 0.18, 95% CI (0.039–0.784)], and unable to get masks [AOR = 0.12, 95% CI (0.026–0.543)]. The participants who missed counseling services were 55 (25.9%). In multivariate logistic regression, the following were statistically significant: age ≥ 55 [AOR = 0.21, 95% CI (0.078–0.570)], fear of COVID-19 [AOR = 0.11, 95% CI (0.013–0.912)], reduced income [AOR = 0.17, 95% CI (0.041–0.699)], unable to get face masks [AOR = 0.19, 95% CI (0.039–0.959)], and partial lockdown [AOR = 0.08, 95% CI (0.008–0.790)]. Conclusions The COVID-19 had a significant burden on patients with HIV to attend their routine clinical care and treatment, which may lead to treatment failure and drug resistance. The impact was on their appointments for medication refills and clinical and laboratory follow-ups. Targeted initiatives are needed to sustain HIV clinical care and treatment services and improve the well-being of people living with HIV.